2019
DOI: 10.3390/heritage2030127
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Stone Heritage in the Painted Desert: Employing the Rock Art Stability Index in the Petrified Forest National Park, Arizona

Abstract: Located in northeastern Arizona (USA), Petrified Forest National Park (PEFO) presents a unique story of both geologic and human history. Though perhaps most well-known for its abundant petrified wood and being part of the Painted Desert, visitors are often surprised when they discover PEFO hosts many ancient petroglyph sites. Over the years, many attempts have been made to record the petroglyph sites, but nothing has been done to assess their geomorphic stability. To address this shortcoming, we employed the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Different instruments (including low-cost instruments) and methodologies have been applied to perform structure-from-motion photogrammetry on rock art panels. Moreover, several indexes exist to scientifically estimate the stability of rock art and they are based mostly on biogeomorphology observations and in situ measurements [34,116]. Stability indexes offer the first effective tool to plan investigation and preservation strategies, as in the case of the Rock Art Stability Index [117,118].…”
Section: Methods For Investigation Of Rock Artmentioning
confidence: 99%
“…Different instruments (including low-cost instruments) and methodologies have been applied to perform structure-from-motion photogrammetry on rock art panels. Moreover, several indexes exist to scientifically estimate the stability of rock art and they are based mostly on biogeomorphology observations and in situ measurements [34,116]. Stability indexes offer the first effective tool to plan investigation and preservation strategies, as in the case of the Rock Art Stability Index [117,118].…”
Section: Methods For Investigation Of Rock Artmentioning
confidence: 99%
“…Research has shown that there is a need for developing and testing new methods for assessing the state of preservation of materials and their potential degradation due to exposure to environmental factors. Studies on rock art have traditionally focus on the one hand, on the documentation, understanding and interpretation of the themes depicted by ancient civilizations [60][61][62][63], and on the other hand, on the preservation of paintings and petroglyphs [2,64,65]. Due to the complexity of materials found in rock art paintings, a combination of analytical techniques is often needed to provide a comprehensive identification of the pigment, substrate systems at a particular site [66].…”
Section: Discussionmentioning
confidence: 99%